Ayçiçek Asidik Yağının Enzimatik Hidroliz Reaksiyonunun İncelenmesi - Erdoğan, Füsun (Fen Bilimleri Enstitüsü, 2015)
Deterjan, sabun, kozmetik, tekstil ve boya endüstrisinde geniş bir kullanım alanına sahip olan yağ asitlerinin üretimi, günümüzde kimyasal katalizörler varlığında yüksek sıcaklık ve basınç altında yürütülen sürekli ters akım hidroliz prosesi ile yapılmaktadır. Bu yöntemin çok fazla enerji gerektiren bir proses olması ve termal bozunma sonucu ürün kalitesinin bozulmasından dolayı, yeni arayışlara girilmiş, enzimatik yağ hidrolizinin yağ asitleri üretiminde önemli bir potansiyel oluşturabileceği düşünülerek bu konudaki çalışmalara hız verilmiştir. Bu çalışmada, günümüzde düşük kaliteli sabunların üretiminde ham madde olarak kullanılan, yemeklik yağ üretimi yan ürünü olan ayçiçek asidik yağının Lipase PS Amano mikrobiyal lipazı varlığındaki enzimatik hidroliz reaksiyonu incelenmiştir. Çeşitli enzim miktarı, sıcaklık, enzim/yağ oranı, su ve tampon çözelti içeriğinde yürütülen reaksiyonlarla hidroliz reaksiyonunun optimum koşullarının belirlenmesine çalışılmıştır. Ayçiçek asidik yağının Lipase PS Amano mikrobiyal lipazı katalizörlüğünde gerçekleştirilen hidroliz reaksiyonu için optimum enzim /yağ oranının 0.05 olduğu gözlenmiştir. Bu enzim/yağ oranında optimum sıcaklık 45°C ve optimum su miktarı nötral gliseridlerin %80i olarak belirlenmiştir. 45°Cde, 0.05 enzim/yağ oranında, nötral gliseridlerin %80i kadar farklı pHlardaki tampon çözeltiler ile yürütülen hidroliz reaksiyonlarında ise Lipase PS Amano için optimum pHın 7 olduğu görülmüştür.

The production of fatty acids which has wide applications in detergent, soap, cosmetics, textile and paint industries, is realised with the continuous reverse flow hydrolysis under the presence of chemical catalysts, at high temperature and pressure. Since this method is high energy demanding process and thermal denaturation of products becasue of thermal dissociation, new research studies are started and with the consideration of enzymatic hydrolysis will be important potential in the production of fatty acids these studies are accelerated. In this study, enzymatic hydrolysis reaction with the presence of Lipase PS “Amano” microbial lipase for sunflower acid oil which is one of the acid oils mainly that are used as a raw material in low quality soap production, which is by product of edible oil production was examined. With the various amounts of enzyme, temperature, enzyme/acid oil ratio, water and buffer solution contents the reactions were carried out and the optimum conditions were tried to be determined. For the hydrolysis reaction of sunflower acid oil with the presence of Lipase PS “Amano” microbial lipase catalyst the optimum enzyme/acid oil ratio was determined as 0.05. At this enzyme/fatty acid ratio the optiumum temperature was observed as 45°C and the optimum water amount as 80% of neutral glycerids. At the conditions of 45°C and 0.05 enzyme/acid oil ratio, water amount 80% of neutral glycerids various reactions were carried out with differernt buffer solutions and for Lipase PS “Amano” the optimum pH was determined as 7. With the optimum reaction conditions which are determined for sunflower acid oil a hydrolysis reaction for corn acid oil was carried out and it was decided that Lipase PS ”Amano” has a substrat selectivity for sunflower acid oil.
Evaluation Of Enzymatic Hydrolysis Reaction Of Sunflower Acid Oil
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2002
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2002
Keywords: Enzimatik hidroliz; Lipase PS Amano; Ayçiçek Asidik Yağı; Mısırözü Asidik Yağı; Enzymatic Hydrolysis; Lipase PS Amano; Sunflower Acid Oil; Corn Acid Oil